Biological behaviour of primary osteosarcoma of the digits, metacarpal and metatarsal bones in dogs. (21st September 2020) - Tremolada, Giovanni; Thamm, Douglas H.; Milovancev, Milan; Seguin, Bernard
Abstract: Osteosarcoma (OSA) arising from the digits, metatarsal and metacarpal bones is rare and may carry a better prognosis compared with other locations. The aim of this study was to retrospectively evaluate the biological behaviour, the progression free interval (PFI), the survival time (ST) and evaluate the effect of adjuvant chemotherapy for OSA affecting these bones. Medical records from two academic institutions were reviewed and 15 cases were included. Descriptive statistics were used for signalment and history. For estimation of median PFI and median ST, the Kaplan‐Meier method was utilized. The prognostic effect of chemotherapy, lymphocyte and monocyte count was investigated. Log‐rank analysis was used to compare PFI and ST between groups. The overall median PFI and median ST were 377 and 687 days, respectively. No significant differences were noted for any of the variables evaluated. In this study, dogs affected by OSA of digits, metacarpal and metatarsal bones appear to have a longer ST compared with dogs with OSA of other appendicular locations. A study with a larger number of patients is needed to confirm these results and investigate the potential benefit of adjuvant chemotherapy.